Methionine-restricted diet inhibits growth of MCF10AT1-derived mammary tumors by increasing cell cycle inhibitors in athymic nude mice. Issue 1 (December 2016) - Hens, J.; Sinha, I.; Perodin, F.; Cooper, T.; Sinha, R.; Plummer, J.; Perrone, C.; Orentreich, D.
Abstract Background Dietary methionine restriction (MR) improves healthspan in part by reducing adiposity and by increasing insulin sensitivity in rodent models. The purpose of this study was to determine whether MR inhibits tumor progression in breast cancer xenograft model and breast cancer cell lines. Methods Athymic nude mice were injected with MCF10AT1 cells in Matrigel® and fed a diet containing either 0.86 % methionine (control fed, CF), or 0.12 % methionine (MR) for 12 weeks. Plasma amino acid concentrations were measured by UPLC, and proliferation and apoptosis were examined using RT-PCR, immunohistochemistry, and Cell Titer 96® Aqueous One Solution Cell Proliferation assay. Results Mice on the MR diet had reduced body weight and decreased adiposity. They also had smaller tumors when compared to the mice bearing tumors on the CF diet. Plasma concentrations of the sulfur amino acids (methionine, cysteine, and taurine) were reduced, whereas ornithine, serine, and glutamate acid were increased in mice on the MR diet. MR mice exhibited decreased proliferation and increased apoptosis in cells that comprise the mammary glands and tumors of mice. Elevated expression of P21 occurred in both MCF10AT1-derived tumor tissue and endogenously in mammary gland tissue of MR mice. Breast cancer cell lines MCF10A and MDA-MB-231 grown in methionine-restricted cysteine-depleted media for 24 h also up-regulated P21 and P27 gene expression, and MDA-MB-231 cells had decreased proliferation. Conclusion MR hinders cancer progression by increasing cell cycle inhibitors that halt cell cycle progression. The application of MR in a clinical setting may provide a delay in the progression of cancer, which would provide more time for conventional cancer therapies to be effective.